A small protome for a glorious hero: a new bucchero specimen from the “monumental complex” at Tarquinia (VT) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
The finding of a new bucchero protome portraying Hercle with leonté at the “monumental complex” at Tarquinia prompts a brief review of its informative potentials: on one hand, the specimen places itself as a unicum into a well-known local workshop, on the other the subject depicted adds a relevant puzzle piece within a sequence of artifacts that are re-examined for the occasion in order to show the hero’s long lasting relevance for the Etruscan city.